STATEMENTAL CHARACTERISTICS OF ATTRACTS IN ENGLISH SCIENTIFIC TEXTS - Ruziyeva Nigora Ulug’bek qizi (PEDAGOGS, 2025)
Abstract. It is known that the main social function of language is a means of communication, communication and influence. Each language in the world, regardless of which language family it belongs to, has similarities and differences depending on these tasks. In this regard, the comparison of the use of the sign words in the English and Uzbek languages ​​in colloquial speech, scientific and formal methods helps to determine the differences and commonalities between the use of words belonging to different language families, functional and stylistic features.